Scapular kinematic is altered after electromyography biofeedback training. Issue 9 (14th June 2016) - San Juan, Jun G.; Gunderson, Samantha R.; Kane-Ronning, Kai; Suprak, David N.
Abstract: Electromyography (EMG) biofeedback training affords patients a better sense of the different muscle activation patterns involved in the movement of the shoulder girdle. It is important to address scapular kinematics with labourers who have daily routines involving large amounts of lifting at shoulder level or higher. This population is at a heightened risk of developing subacromial impingement syndrome (SAIS). The purpose of this study was to investigate the acute effects of scapular stabilization exercises with EMG biofeedback training on scapular kinematics. Twenty-three healthy subjects volunteered for the study. Electrodes were placed on the upper and lower trapezius, serratus anterior, and lumbar paraspinals to measure EMG activity. Subjects underwent scapular kinematic testing, which consisted of humeral elevation in the scapular plane, before and after biofeedback training. The latter consisted of 10 repetitions of the I, W, T, and Y scapular stabilization exercises. Subjects were told to actively reduce the muscle activation shown on the screen for the upper trapezius during the exercises. The scapular external rotation had a statistically significant difference at all humeral elevation angles ( p <0.004) after biofeedback was administered. After the exercises, the scapula was in a more externally rotated orientation with a mean difference of 6.5°. There were no significant differences found with scapular upward rotation, or posterior tilt at all humeral elevation angles following biofeedback. Scapular kinematics are altered by EMG biofeedback training utilizing scapular stabilization exercises. However, only scapular external rotation was affected by the exercises.